ANALYSIS OF INDONESIA'S DEFENSE DIPLOMACY IN FACING THE CRISIS ON THE KOREAN PENINSULA TO MAINTAIN THE STABILITY OF THE SOUTHEAST ASIAN REGION - Chayu Amrita Nanda; Yoedhi Swastanto; Amarulla Octavian (Indonesia Defense University, 2019)
In a security perspective, the territory of Indonesia and the Southeast Asia region as a whole are strategic areas in economic, political and military aspects. This condition also has complex potential challenges and risks for creating tension among countries. After the Korean War and World War II the development of the crisis on the Korean Peninsula continued. North Korea chose to build and to increase its military capabilities. Indonesia as one of the adjacent countries to the Korean Peninsula, could get an impact to the sovereignty and security of the country. Especially caused by North Korea’s nuclear testing activities. This study aims to determine the form of Indonesian Defense Diplomacy and how the roles of the involved actors in responding to the issue. By using qualitative research methods, this study discusses the issue with constructivist theory and the concept of defense diplomacy for the analysis. The result of this research is a form of Indonesian defense diplomacy in response to the crisis on the Korean Peninsula.Keywords: ASEAN, defense diplomacy, denuclearization, defense strategy, regional security